TRADITIONAL INSTITUTIONS AS QUASI-LEGITIMATION IN VILLAGE DEVELOPMENT - Gajah, Nurhamidah; Hamdani, R.; Lubis, Zulkifli; Hasugian, Jonner (Proceeding International Seminar of Islamic Studies, 2024)
The existence of traditional leaders who play a very important role in village development are traditional leaders, the term for traditional leaders in the villages in South Tapanuli Regency, North Sumatra Province area is Hatobangon. As an elder person in a clan or a Huta/village, Hatobangon plays a very important role in resolving problems that occur. The role of Hatobangon is to preserve, maintain, and encourage the community to maintain the traditions of their ancestors to work together with the village, sub-district, and district governments. Hatobangon also became quasi in protecting forests, rivers, and buffer areas to realize Ministry of Forestry or International NGO programs. This research aims to examine the partnership that occurs between the government and Hatobangon in village development in South Tapanuli Regency and the inhibiting and supporting factors between the government and Hatobangon in developing villages. The approach used in this study is qualitative and data collection techniques in this research used observation, interviews, and documentation studies. The Partnership Model in Increasing Hatobangon 's Capacity as a Quasi hopefully can be sustainable as a traditional institution in the Angkola Community. The partnership pattern that occurs between the government and Hatobangon in developing villages is the Subordinate union of partnership, Linear union of partnership, and Linear Collaborative of Partnership.